Service quality perception and students’ satisfaction in higher learning institutions in Tanzania: The servqual model - Victor, William Bwachele (2024)
In developing the nation's economic and social status, the Tanzanian government dev elops human capital by establishing more local higher education learning institutions (HLIs). Nevertheless, the growing count of student enrolments and the establishment of local HLIs decrease the proportion of public financial aid for each student and HLI . As a result, students evaluate their HLIs' service quality (SQ) related to their study e nvironment and the provision of teaching and learning resources as they pay higher tuition fees. Hence, the SQ parameters are used to determine student satisfaction. The widespread student dissatisfaction of HLIs student services with social media networks marks the importance of understanding students' perceived SQ dimensions. A preliminary study was carried out to conceptualize the SQ dimensions using content analysis. The result shows that seven SQ dimensional v ariables were elicited; the five-dimensional variables are explained in the service quality model (SERVQUAL) - tangibility, reliability, responsiveness, assurance, and empathy – and another twodimensional variable is perceived transparency and trust. Subsequently, a closed-ended questionnaire was conducted using a drop-off and pick-up self-administered method to test the hypothetical relationship between the seven elicited SQ dimensional variables and student satisfaction. From selected HLIs in Tanzania's coastal region, 398 final-year students were picked using multistage cluster sampling. The main data were analyzed using structural equation modeling partial least square approach. The result shows that reliability and trust in institution dimensional variables are significant predictors, and perceived transparency is an essential external variable to trust. Also, trust in an institution partially mediated the relationship between perceived transparency and student satisfaction. The tangibility, responsiven ess, assurance, and empathy dimensional variables are non-significant predictors. Based on the study's findings, recommendations are suggested to the academics to enrich the service quality literature and to public and private policymakers in planning tactical strategies.